Bioreactors in tissue engineering—principles, applications and commercial constraints. Issue 3 (19th November 2012) - Hansmann, Jan; Groeber, Florian; Kahlig, Alexander; Kleinhans, Claudia; Walles, Heike
Abstract Bioreactor technology is vital for tissue engineering. Usually, bioreactors are used to provide a tissue‐specific physiological in vitro environment during tissue maturation. In addition to this most obvious application, bioreactors have the potential to improve the efficiency of the overall tissue‐engineering concept. To date, a variety of bioreactor systems for tissue‐specific applications have been developed. Of these, some systems are already commercially available. With bioreactor technology, various functional tissues of different types were generated and cultured in vitro. Nevertheless, these efforts and achievements alone have not yet led to many clinically successful tissue‐engineered implants. We review possible applications for bioreactor systems within a tissue‐engineering process and present basic principles and requirements for bioreactor development. Moreover, the use of bioreactor systems for the expansion of clinically relevant cell types is addressed. In contrast to cell expansion, for the generation of functional three‐dimensional tissue equivalents, additional physical cues must be provided. Therefore, bioreactors for musculoskeletal tissue engineering are discussed. Finally, bioreactor technology is reviewed in the context of commercial constraints.